Conflicting rationalities and the governance of homelessness in Ward 64, Cape Town - Cousins, Danica (Department of Sociology, 2023)
In South Africa there is no national mandate or coherent policy framework around the issue of homelessness. Therefore no budget, laws or policies can be used to mobilize and unify the actors involved in the governance of homelessness. This, accompanied by an out of date City of Cape Town Street People Policy, has left the question of "who is responsible for service provision to street-based people'' ambiguous and politically inflammatory. This study explores the value of understanding the problem of homelessness and the way it is governed at a local level. Therefore, it examines how the multiple and varied understandings of street-based people affect governance of the issue of homelessness in Ward 64, Cape Town. To do so, an ethnographic case study approach was combined with Watson's theory of Conflicting Rationalities and used to examine the sociological experiences of street-based people. What resulted was a framework which allowed the “logics and imperatives” of homelessness to be understood through a rationality of survival. Approaching an investigation of homelessness through this rationality validates and reasons with the experiences and survivalist activities of street-based people. To investigate the governance of homelessness in the Ward, data from multiple in-depth interviews and fieldwork observations was analysed through a nodal governance framework. The results indicate that nodes whose engagement with street-based people is motivated by the complaints of, and their responsibility to City and Ward residents, deploy reactive technologies. Alternatively, nodes whose primary responsibility is to street-based people employ a variety of developmental responses. The success of a developmental response is largely reliant on effective partnerships. However, organisational pride and competition for funding present significant challenges to these partnerships and, therefore to the effective governance of homelessness. The case study presented in this thesis highlights the value of Ward level research and interventions into homelessness. Accepting that street-based people are not a homogenous group leads to an understanding that homelessness will not present the same in different areas. Therefore, the facilitation of realistic and meaningful strategies to govern homelessness requires a local understanding of the interaction between the multiple rationalities of both street-based people and governance stakeholders.